Method for producing hydroxide containing nickel and cobalt

The method addresses the inefficiencies and high costs of existing nickel hydroxide production by using a multi-step process involving water washing, alkali washing, leaching, and pyrolysis precipitation to produce high-purity nickel and cobalt hydroxides from impure raw materials, thereby enhancing cost-effectiveness and environmental sustainability.

JP7662112B1Active Publication Date: 2025-04-15SUMITOMO METAL MINING CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2024569793
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2023-06-22
Filing Date
2024-06-18
Publication Date
2025-04-15
Estimated Expiration
2044-06-18

AI Technical Summary

Technical Problem

Existing methods for producing nickel hydroxide as a precursor for lithium-ion secondary battery electrodes are costly and inefficient, especially when using refined metallic nickel, which requires additional processing steps and separation of cobalt, leading to increased costs and environmental concerns due to sodium sulfate by-products.

Method used

A method involving a water washing step, a first and second alkali washing step using sodium hydroxide solutions, a leaching step with an aqueous ammonia solution, and a pyrolysis precipitation step to produce nickel and cobalt hydroxides from mixed hydroxides containing impurities, thereby avoiding the use of refined metallic nickel and reducing costs.

Benefits of technology

This method allows for the efficient production of high-purity nickel and cobalt hydroxides that can be used as precursors for lithium-ion battery electrodes, even when the raw material contains diverse impurities, thus reducing production costs and environmental impact.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007662112000001_ABST
    Figure 0007662112000001_ABST
Patent Text Reader

Abstract

The present invention provides a method for producing a hydroxide containing nickel (Ni) and cobalt (Co) that can be used as a precursor for a positive electrode active material, even if the raw material contains various impurities. [Solution] A method for producing hydroxides containing Ni and Co, comprising the steps of: washing NiCo mixed hydroxide with water; a first alkaline washing step of washing the washed NiCo mixed hydroxide with a basic aqueous solution of a predetermined concentration and temperature for a predetermined washing time; a step of leaching the washed NiCo mixed hydroxide with an aqueous ammonia solution of a predetermined ammonium carbonate and / or ammonium bicarbonate concentration at a predetermined temperature; a thermal decomposition precipitation step of heating the obtained leachate containing Ni and Co at a predetermined temperature to precipitate these Ni and Co as hydroxides; and a second alkaline washing step of washing the precipitated hydroxides with a basic aqueous solution of a predetermined concentration and temperature for a predetermined washing time.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for producing hydroxides containing nickel and cobalt. [Background technology]

[0002] Lithium ion secondary batteries, which are charged and discharged by the movement of lithium ions between a positive electrode and a negative electrode, have a high energy density and are not easily deteriorated even when repeatedly charged and discharged, so in recent years demand has been increasing for them as batteries for electronic devices such as mobile phones and laptops, as driving power sources for electric vehicles and the like, storage batteries for smart grids, etc. A lithium ion secondary battery has a basic structure consisting of a positive electrode and a negative electrode facing each other with a separator therebetween, and an electrolyte consisting of an organic electrolytic solution filled between them.

[0003] The active material contained in the positive electrode is a metal oxide having a layered rock salt type or spinel type crystal structure containing lithium. Specifically, lithium cobalt oxide (LiCoO2), lithium nickel oxide (LiNiO2), ternary lithium nickel cobalt manganese oxide (NCM), lithium nickel cobalt aluminum oxide (NCA), lithium manganese oxide (LiMn2O4), etc. can be mentioned, and they are used according to the application and purpose. These active materials can be produced by mixing lithium hydroxide particles with metal hydroxide particles as a precursor and baking the mixture.

[0004] The above metal hydroxide particles can be produced by crystallization by adjusting the pH of a solution containing the target metal salt. For example, in the production of a precursor of lithium nickel cobalt manganese oxide, an aqueous solution of sodium hydroxide is added to an aqueous solution containing the raw materials nickel sulfate, cobalt sulfate, and manganese sulfate, and a mixed hydroxide containing nickel hydroxide, cobalt hydroxide, and manganese hydroxide can be produced by the neutralization reaction that occurs as a result. However, in the above neutralization reaction of the raw material nickel sulfate, sodium sulfate (mirabilite) produced as a by-product in an equimolar amount with nickel hydroxide as shown in the following formula 1 can be a problem. That is, since the total amount of sodium sulfate in wastewater is regulated in some areas, there are cases where it is necessary to install treatment facilities at a cost to meet the wastewater standards, or to limit the production amount of nickel hydroxide to suppress the discharge of sodium sulfate. [Formula 1] NiSO4+2NaOH → Ni(OH)2+Na2SO4

[0005] In order to avoid the above problems, a method for producing nickel hydroxide that does not produce sodium sulfate as a by-product has been proposed. For example, Patent Document 1 proposes a technique in which oxygen is introduced into an aqueous ammonia solution containing powder of metallic nickel to cause the metallic nickel to leach into the aqueous ammonia solution, seed crystals are added as necessary to the resulting aqueous ammonia solution containing nickel and hydroxyl ions, and then the aqueous ammonia solution is distilled under atmospheric pressure or reduced pressure to precipitate and recover nickel hydroxide. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] Japanese Patent Application Publication No. 10-324524 Summary of the Invention [Problem to be solved by the invention]

[0007] By using the technology of the above-mentioned Patent Document 1, nickel hydroxide can be produced without producing sodium sulfate as a by-product, but the technology of Patent Document 1 uses metallic nickel as a precursor raw material, and therefore is not economically advantageous. That is, metallic nickel is generally produced by leaching nickel from intermediate raw materials such as matte, sulfide, or hydroxide obtained by processing nickel ore using acid or chlorine, and then separating impurities leached together with the nickel by a refining process and then performing electrowinning, so that the metallic nickel finally obtained has a plate or lump shape. Therefore, in order to efficiently leach metallic nickel with an ammonia aqueous solution, a process of processing the plate or lump metallic nickel into a powder is required.

[0008] In addition, some positive electrode active materials contain cobalt, such as the above-mentioned NCM and NCA, and in this case, there is no particular problem if the precursor of the positive electrode active material contains cobalt in addition to nickel, and in many cases it is preferable to contain a certain amount of cobalt. However, although many of the raw materials used in the production of the above-mentioned metallic nickel generally contain cobalt, cobalt is separated and removed from nickel by a refining method such as solvent extraction in a pre-process of electrowinning, resulting in unnecessary separation costs. In this way, the method of producing nickel hydroxide using refined metallic nickel as a raw material requires many processes that cause cost increases, so it is preferable from the viewpoint of production costs if a hydroxide containing nickel and cobalt that can be used as a precursor of the positive electrode active material of a lithium-ion secondary battery can be produced using, for example, unrefined raw materials containing a wide variety of impurities obtained by processing nickel oxide ore or scrap as an alternative raw material.

[0009] The present invention has been made in consideration of the above circumstances, and has an object to provide a method capable of producing a hydroxide containing nickel and cobalt that can be used as a precursor of a positive electrode active material for a lithium ion secondary battery, even if the raw material contains a larger variety of impurities than refined metallic nickel. [Means for solving the problem]

[0010] In order to achieve the above object, the method for producing a hydroxide containing nickel and cobalt according to the present invention includes a water washing step of washing a particulate nickel-cobalt mixed hydroxide with water, a first alkali washing step of washing the washed nickel-cobalt mixed hydroxide with an aqueous sodium hydroxide solution having a sodium hydroxide concentration of 1.0 mol / L or more and 8.0 mol / L or less and a liquid temperature of 10°C or more and 90°C or less for 0.50 hours or more and 2.0 hours or less, and a second alkali washing step of washing the nickel-cobalt mixed hydroxide washed in the first alkali washing step with an aqueous sodium hydroxide solution having an ammonium carbonate and / or ammonium hydrogen carbonate concentration of 0.50 mol / L or more and 4.1 mol / L or less. the leaching process includes a leaching step in which a slurry having a temperature of 0° C. to 60° C. is leached using an ammonia-containing aqueous solution containing the ammonia water; a thermal decomposition precipitation step in which the leachate containing nickel and cobalt obtained by the leaching process is heated at a temperature of 60° C. to 100° C. for 0.50 to 2.0 hours to precipitate the nickel and cobalt as hydroxides; and a second alkali washing step in which the precipitated hydroxides are washed using an aqueous sodium hydroxide solution having a sodium hydroxide concentration of 1.0 mol / L to 8.0 mol / L and a liquid temperature of 10° C. to 90° C. for 0.50 to 2.0 hours. Effect of the Invention

[0011] According to the present invention, even if a raw material contains more impurities than refined metallic nickel, it is possible to produce a hydroxide containing nickel and cobalt that can be used as a precursor of a positive electrode active material for a lithium ion secondary battery. [Brief description of the drawings]

[0012] [Figure 1] FIG. 1 is a block flow diagram of an embodiment of a method for producing a hydroxide containing nickel and cobalt according to the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] Hereinafter, an embodiment of the method for producing a hydroxide containing nickel and cobalt according to the present invention will be described with reference to FIG. 1. The method for producing a hydroxide according to the embodiment of the present invention is a method for producing a hydroxide containing nickel and cobalt that can be used as a precursor of a positive electrode active material of a lithium ion secondary battery (hereinafter also referred to as a purified nickel-cobalt mixed hydroxide), and the mixed hydroxide containing nickel and cobalt used as a raw material here contains, in addition to the target metals nickel and cobalt, impurities such as calcium, magnesium, zinc, sulfur, silicon, manganese, iron, aluminum, etc. The mixed hydroxide of nickel and cobalt containing such various impurities (hereinafter also simply referred to as nickel-cobalt mixed hydroxide) may be referred to as a mixed hydroxide precipitate (MHP).

[0014] Specifically, the method for producing a hydroxide containing nickel and cobalt according to an embodiment of the present invention includes a water washing step in which a particulate nickel-cobalt mixed hydroxide is washed with water at room temperature, a first alkaline washing step in which the washed nickel-cobalt mixed hydroxide is washed with an alkaline washing solution having a predetermined alkali concentration and a predetermined liquid temperature for a predetermined time, a leaching step in which the nickel-cobalt mixed hydroxide washed in the first alkaline washing step is leached with an ammonia-containing aqueous solution having a predetermined liquid temperature and containing ammonium carbonate or ammonium hydrogen carbonate at a predetermined concentration to leach the nickel and cobalt in the form of an ammine complex, a thermal decomposition precipitation step in which the leachate containing nickel and cobalt obtained by the leaching treatment is heated under predetermined conditions to thermally decompose the ammine complex into ammonia and carbonic acid and precipitate nickel and cobalt as hydroxides, and a second alkaline washing step in which the precipitated hydroxide is washed with an alkaline washing solution having a predetermined alkali concentration and a predetermined liquid temperature for a predetermined time. Each of these steps will be described in more detail below.

[0015] [Water washing process] The water washing step is a step of removing mainly calcium and magnesium contained as impurities in the raw material nickel-cobalt mixed hydroxide having a particulate form by using washing water. The liquid temperature of the washing water used in this water washing step is preferably 10°C or higher and 90°C or lower, more preferably room temperature. There is no particular limitation on the specific washing method, but for example, a method can be mentioned in which the nickel-cobalt mixed hydroxide is added to washing water previously charged in a container equipped with a stirrer, and the mixture is kept in the form of a slurry for about 0.50 to 1.0 hours while being stirred with the stirrer. After washing, the slurry is introduced into a solid-liquid separator such as a centrifuge or a filter for solid-liquid separation, whereby the washed wet nickel-cobalt mixed hydroxide can be recovered.

[0016] [First alkaline cleaning process] The first alkaline washing step is a step of removing mainly zinc, sulfur and silicon, which are impurities that are difficult to remove in the preceding water washing step, by using an alkaline washing solution. The type of alkaline washing solution used in this first alkaline washing step is not particularly limited, and an aqueous solution of caustic soda can be preferably used. When caustic soda is used, the concentration of sodium hydroxide in the alkaline washing solution is preferably 1.0 mol / L or more and 8.0 mol / L or less. A specific embodiment of the first alkaline washing step is illustrated in Reference Example 3 described later.

[0017] If the sodium hydroxide concentration is less than 1.0 mol / L, the removal of zinc, sulfur, and silicon may be insufficient. In particular, since zinc is contained in the mixed hydroxide of nickel and cobalt recovered as a precipitate in the subsequent thermal decomposition precipitation step, even if the zinc is washed in the second alkaline washing step following the thermal decomposition precipitation step, the opportunity for the alkaline washing solution to come into contact with the zinc inside the mixed hydroxide is hindered, making removal difficult, so it is desirable to sufficiently remove zinc in the first alkaline washing step.

[0018] On the other hand, when the concentration of sodium hydroxide exceeds 8.0 mol / L, there is an advantage that zinc, sulfur and silicon can be sufficiently removed, but nickel hydroxide and cobalt hydroxide may be oxidized to oxides. When hydroxides are converted to oxides in this way, it is likely to cause inconveniences such as difficulty in leaching nickel and cobalt in the subsequent leaching process. It is more preferable that the concentration of sodium hydroxide is 4.0 mol / L or more and 8.0 mol / L or less, because oxidation is suppressed while removing zinc and sulfur, and the above-mentioned inconveniences in the leaching process are easily avoided. On the other hand, when the concentration of sodium hydroxide is 1.0 mol / L or more and less than 4.0 mol / L, the removal rate of zinc is lower than when the concentration is 4.0 mol / L or more, but oxidation tends to be suppressed, so it is rather advantageous from the viewpoint of reducing the loss of nickel and cobalt. Therefore, it is preferable to appropriately select the concentration of sodium hydroxide depending on the use and purpose of the hydroxide containing nickel and cobalt (that is, the purified nickel-cobalt mixed hydroxide) as a precursor of the positive electrode active material of the lithium ion secondary battery.

[0019] The temperature of the alkaline cleaning solution used in the first alkaline cleaning step is preferably 10° C. to 90° C., more preferably 70° C. to 90° C. If the solution temperature is less than 10° C., the removal of zinc, sulfur, and silicon may be insufficient, and if the solution temperature exceeds 70° C., the removal rates of zinc, sulfur, and silicon can be maintained at a high level. However, if the solution temperature exceeds 90° C., the removal rates of zinc, sulfur, and silicon do not improve significantly, and instead, the loss of moisture due to evaporation becomes excessive, which is disadvantageous in terms of cost.

[0020] The washing time of the first alkaline washing step is preferably 0.50 hours or more and 2.0 hours or less, and more preferably 0.50 hours or more and 1.0 hours or less. By setting the washing time to 0.50 hours or more, the desired removal rate of zinc, sulfur, and silicon can be achieved. On the other hand, even if the washing time exceeds 1.0 hours, the removal rate of these elements does not improve significantly, so by setting the washing time to 1.0 hours or less, zinc, sulfur, and silicon can be removed efficiently at low cost. In addition, since the particles of the nickel-cobalt mixed hydroxide washed in the previous water washing step often aggregate to form aggregates, if the washing time is less than 0.50 hours, it is difficult to make the alkaline washing solution reach the inside of the aggregates even if the alkaline washing is performed while stirring, and as a result, the desired removal rate cannot be obtained. On the other hand, if the washing time exceeds 2.0 hours, nickel hydroxide and cobalt hydroxide are easily oxidized, and the oxides of nickel and cobalt thus produced may be difficult to leach in the next leaching step.

[0021] As described above, zinc is easily included in the mixed hydroxide of nickel and cobalt produced in the thermal decomposition precipitation step, and in this case, even if washing is performed in the second alkaline washing step following the thermal decomposition precipitation step, it is difficult to remove zinc, so it is desirable to determine various washing conditions in this first alkaline washing step, i.e., sodium hydroxide concentration, washing temperature, and washing time, taking into consideration the zinc removal rate in the second alkaline washing step. Specifically, in order to obtain a desired zinc quality in the hydroxide containing nickel and cobalt obtained through the second alkaline washing step, it is preferable to remove zinc in this first alkaline washing step, for example, with the aim of achieving a zinc removal rate of preferably 15% or more, more preferably 50% or more, and even more preferably about 80 to 90%.

[0022] That is, in the first alkaline washing step, if the removal rates of zinc and sulfur are 15% or more and 75% or more, respectively, it is possible to achieve the desired quality generally required for a hydroxide containing nickel and cobalt (i.e., a purified nickel-cobalt mixed hydroxide) as a precursor of a positive electrode active material of a lithium ion secondary battery obtained through a subsequent step. When a higher quality is required as a precursor of a positive electrode active material of a lithium ion secondary battery, it is desirable to adopt conditions in this first alkaline washing step that result in the removal rates of zinc and sulfur of 50% or more and 90% or more, respectively.

[0023] There is no particular limitation on the specific washing method using an alkaline washing solution, but for example, a method can be mentioned in which nickel-cobalt mixed hydroxide is added to an alkaline washing solution previously placed in a container equipped with a stirrer and a jacket, and the solution is stirred while controlling the temperature by introducing, for example, steam into the jacket, thereby maintaining the solution in a slurry state for a predetermined time. After the alkaline washing, the slurry is introduced into a solid-liquid separator such as a centrifuge or a filter for solid-liquid separation, whereby the alkaline-washed wet nickel-cobalt mixed hydroxide can be recovered.

[0024] In the solid-liquid separation after the alkaline washing, the washing effluent discharged to the liquid phase side contains impurities such as zinc, sulfur, and silicon, so it is preferable to remove these impurities from the washing effluent by an impurity removal method such as a precipitation method. This allows the washing effluent to be repeatedly used as the alkaline washing liquid. Here, the precipitation method is a method of extracting solutes dissolved in a solution as precipitated particles, for example, by changing the washing effluent from an unsaturated state to a supersaturated state, thereby promoting the generation and growth of crystal nuclei to obtain the precipitated particles.

[0025] [Leaching process] The leaching step is a step of leaching the nickel-cobalt mixed hydroxide that has been alkaline washed in the first alkaline washing step of the previous step with an ammonia-containing aqueous solution. Specifically, water is charged into a vessel equipped with a stirrer and a jacket, and ammonia water (NH4OH) and ammonium carbonate ((NH4)2CO3) are added thereto to prepare an ammonia-containing aqueous solution. To prepare this ammonia-containing aqueous solution, ammonium hydrogen carbonate (NH4HCO3) may be used instead of or in addition to ammonium carbonate. Note that FIG. 1 illustrates a case where only ammonium hydrogen carbonate is used. Next, the nickel-cobalt mixed hydroxide particles that have been washed in the first alkaline washing step of the previous step are put into the vessel containing the ammonia-containing aqueous solution prepared as described above, and a slurry having a homogeneous concentration is prepared by stirring and mixing with the stirrer.

[0026] In this state, the slurry temperature is maintained at 0°C or higher and 60°C or lower, preferably 20°C or higher and 50°C or lower, to perform the leaching treatment. As a result, nickel ions and cobalt ions can be leached from the nickel-cobalt mixed hydroxide particles, as shown in Reference Example 4 described later. On the other hand, manganese, iron, and aluminum, which are hardly leached in this leaching process, remain as leaching residue. After the leaching treatment, the slurry is introduced into a solid-liquid separation device such as a centrifuge or a filter, so that the leachate can be separated from the leaching residue. If the slurry temperature is below 0°C, the solubility of ammonium carbonate and ammonium hydrogen carbonate in water decreases, and they become supersaturated and precipitate, making it difficult to leach them well. Conversely, if the slurry temperature exceeds 60°C, ammonium carbonate and ammonium hydrogen carbonate are thermally decomposed, and both nickel and cobalt are difficult to maintain the form of an ammine complex, making it difficult to leach them well in this case as well. In addition, if the slurry temperature is set to 20°C or higher, the reaction rate can be increased, so that the production amount per unit time can be increased.

[0027] When ammonium carbonate is used to prepare the above-mentioned ammonia-containing aqueous solution, the ammonium carbonate concentration in the above-mentioned ammonia-containing aqueous solution is preferably in the range of 0.50 mol / L to 4.1 mol / L, more preferably in the range of 1.5 mol / L to 3.5 mol / L, and most preferably in the range of 2.0 mol / L to 3.0 mol / L. If the ammonium carbonate concentration is less than 0.50 mol / L, it is almost impossible to leach out, and if it is less than 1.5 mol / L, the leaching rate may decrease. On the other hand, even if the ammonium carbonate concentration exceeds about 3.5 mol / L, the leaching rate hardly improves, and the chemical cost increases, which is not preferable. Furthermore, if the ammonium carbonate concentration exceeds 4.1 mol / L, the ammonium carbonate becomes supersaturated and precipitates, which may have an adverse effect on the leaching treatment. The ammonium carbonate concentration can be measured by absorptiometry, ion chromatography, etc., and if the ammonium carbonate concentration is found to be outside the above range, it can be adjusted by adjusting the amount of ammonium carbonate added.

[0028] In addition, even when ammonium hydrogen carbonate is used instead of ammonium carbonate in the preparation of the above-mentioned ammonia-containing aqueous solution, the concentration of ammonium hydrogen carbonate in the ammonia-containing aqueous solution is preferably in the range of 0.50 mol / L or more and 4.1 mol / L or less, more preferably in the range of 1.5 mol / L or more and 3.5 mol / L or less, and most preferably in the range of 2.0 mol / L or more and 3.0 mol / L or less, similarly to the above.

[0029] In addition, the ammonia-containing aqueous solution used in the leaching treatment preferably has a free ammonia concentration in the range of 0.10 to 1.3 mol / L, which allows nickel and cobalt to be leached stably in the form of ammine complexes. If the free ammonia concentration is less than 0.10 mol / L, the formation of ammine complexes may become unstable, while if it exceeds 1.3 mol / L, it has almost no effect on the stable leaching in the form of the amine complexes, and is undesirable because it increases costs and increases the load on wastewater treatment. Note that free ammonia refers to molecular ammonia (NH3), and its concentration can be determined by separating the NH3 form by distillation and then converting it into NH4. + and then measured by absorptiometry. If the free ammonia concentration is outside the above range, it can be adjusted by adjusting the amount of aqueous ammonia added.

[0030] In the manufacturing method of the hydroxide containing nickel and cobalt according to the embodiment of the present invention, the mixed hydroxide of nickel and cobalt containing various impurities to be removed is used as a raw material, and therefore, in the leaching step, the mixed hydroxide of nickel and cobalt that has been subjected to alkaline washing in the first alkaline washing step in the previous step is assumed to be leached with an ammonia-containing aqueous solution. However, the present invention is not limited to this, and as shown in Reference Example 5 described later, for example, the leaching treatment can be performed on a mixed sulfide containing nickel and cobalt instead of the mixed hydroxide of nickel and cobalt. In this case, the mixed sulfide containing nickel and cobalt can be produced by a high-pressure acid leaching method called HPAL (High Pressure Acid Leach) method, in which sulfuric acid is added to nickel oxide ore under high temperature and high pressure to perform acid leaching. Even when the leaching treatment is performed on such a mixed sulfide, both nickel and cobalt form ammine complexes, so that nickel and cobalt can be precipitated as hydroxides and recovered as precipitates by thermal decomposition in the thermal decomposition precipitation step subsequent to this leaching treatment, as shown in Reference Example 6 described later.

[0031] Specifically, water is first placed in a vessel equipped with a stirrer, and ammonia water (NH4OH) and ammonium carbonate ((NH4)2CO3) are added thereto to prepare an ammonia-containing aqueous solution. Alternatively, the ammonia-containing aqueous solution may be prepared by adding ammonium bicarbonate (NH4HCO3) instead of or in addition to ammonium carbonate. Nickel-cobalt mixed sulfide particles are placed in the vessel containing the ammonia-containing aqueous solution prepared in this manner, and the mixture is stirred and mixed with the stirrer to prepare a slurry having a uniform concentration. In this state, air or oxygen gas is blown into the slurry to create an oxidizing condition, thereby performing a leaching treatment. This allows nickel ions and cobalt ions to be leached from the nickel-cobalt mixed sulfide particles.

[0032] In the leaching treatment, the temperature of the slurry is preferably maintained at 20° C. to 50° C., which can promote the leaching reaction. When preparing an ammonia-containing aqueous solution by adding ammonium carbonate in the leaching treatment, the ammonium carbonate concentration in the ammonia-containing aqueous solution is preferably adjusted to within a range of 0.50 mol / L to 4.1 mol / L, more preferably within a range of 1.5 mol / L to 3.5 mol / L, and most preferably within a range of 2.0 mol / L to 3.0 mol / L.

[0033] [Pyrolysis and precipitation process] The thermal decomposition precipitation step is a step in which the leachate produced in the previous leaching step is heated, and the nickel and cobalt ammine complexes are thermally decomposed to precipitate the nickel and cobalt as hydroxides, which are then recovered as a precipitate. In this thermal decomposition precipitation step, it is preferable to stir the mixture while blowing in an oxidizing agent such as air, which promotes the oxidation of cobalt, and as shown in Reference Example 1 described below, it becomes possible to recover both nickel and cobalt as hydroxides with a recovery rate of 90% or more. That is, the cobalt ammine complex is usually converted to divalent cobalt by thermal decomposition, but by oxidizing it to trivalent cobalt, the recovery of the hydroxides is promoted. It is preferable to recover the ammonia and carbonic acid generated by thermal decomposition in this thermal decomposition precipitation step and reuse them as ammonia water containing ammonium carbonate or ammonium hydrogen carbonate in the previous leaching step.

[0034] In this thermal decomposition precipitation step, it is preferable to heat the liquid so that the liquid temperature is 60° C. or more and 100° C. or less. If the liquid temperature is less than 60° C., it becomes difficult to decompose the ammine complexes of nickel and cobalt, and the proportion of ammine complexes that remain stable in the form of these ammine complexes increases, making it difficult to generate precipitates. The higher the temperature, the more efficiently the ammine complexes of nickel and cobalt are decomposed, but a liquid temperature exceeding 100° C. is undesirable from an economical point of view because of the high facility costs and energy consumption costs.

[0035] Even if the liquid temperature is adjusted to within the temperature range of 60°C to 100°C in the thermal decomposition precipitation step as described above, if the holding time is too short, the progress of the thermal decomposition reaction will be insufficient, making it difficult to achieve the desired recovery rate. Therefore, in this thermal decomposition precipitation step, it is preferable to hold the liquid temperature within the temperature range of 60°C to 100°C for 0.50 hours to 2.0 hours. This prevents the problem of nickel and cobalt remaining in large amounts in the form of ammine complexes in the treatment liquid after the thermal decomposition precipitation step, and increases the recovery rate of nickel-cobalt mixed hydroxide.

[0036] In the leaching process, which is a process prior to the thermal decomposition precipitation process, manganese may be leached depending on the leaching conditions. In this case, the impurity manganese will form an ammine complex in the leaching solution in the same way as nickel and cobalt. Since the manganese ammine complex has a lower thermal decomposition temperature than the nickel and cobalt ammine complexes, manganese is more likely to undergo a thermal decomposition reaction and form a precipitate than nickel and cobalt. Therefore, as described above, within the temperature range of 60°C to 100°C, the precipitate formed within less than 0.50 hours after reaching the lower limit temperature in the above temperature range is likely to contain more manganese, so it is preferable to discard or recover the precipitate formed within this time period and use it again as a raw material for the leaching process. On the other hand, even if the above retention time exceeds 2.0 hours, the amount of precipitated nickel-cobalt mixed hydroxide hardly increases.

[0037] [Second alkaline cleaning process] The second alkaline washing step is a step in which the nickel-cobalt mixed hydroxide recovered in the previous pyrolysis precipitation step is washed with an alkaline washing solution. This removes zinc, sulfur, and silicon that could not be completely removed in the above-mentioned first alkaline washing step, as well as carbon derived from the ammonium carbonate and ammonium bicarbonate added in the leaching step, and makes it possible to produce a hydroxide containing high-purity nickel and cobalt with extremely few impurities that can be suitably used as a positive electrode active material for lithium-ion secondary batteries (i.e., a purified nickel-cobalt mixed hydroxide).

[0038] The type of alkaline cleaning solution used in this second alkaline cleaning step is not particularly limited, and an aqueous caustic soda solution can be suitably used, as in the first alkaline cleaning step described above. When caustic soda is used, the concentration of sodium hydroxide in the alkaline cleaning solution is preferably 1.0 mol / L or more and 8.0 mol / L or less, and in particular, the lower limit of the sodium hydroxide concentration is more preferably 2.0 mol / L or more. This makes it possible to maintain a high removal rate of carbon and sulfur impurities, as shown in Reference Example 2 described later.

[0039] In addition, when zinc is contained, it is present mainly in the form of being included in the nickel-cobalt mixed hydroxide produced in the thermal decomposition precipitation step as described above, and therefore the removal rate is lower than that in the first alkali washing step, but the zinc removal rate can be improved to some extent by setting the sodium hydroxide concentration higher. If the sodium hydroxide concentration is less than 1.0 mol / L, there is a risk that the removal of zinc, sulfur, and carbon will be insufficient, and conversely, if it exceeds 8.0 mol / L, there is an advantage that zinc and sulfur can be sufficiently removed, but nickel hydroxide and cobalt hydroxide may be oxidized to oxides, in which case the recovery rate as hydroxides will decrease and the quality of the refined nickel and cobalt mixed hydroxide precursor may deteriorate.

[0040] In this second alkaline washing step, as in the first alkaline washing step, the liquid temperature of the alkaline washing liquid is preferably 10°C or higher and 90°C or lower, more preferably 70°C or higher and 90°C or lower. If the liquid temperature is lower than 10°C, the removal of zinc and sulfur that were not completely removed in the first alkaline washing step and the removal of carbon derived from ammonium carbonate, etc. added in the leaching step may be insufficient, while the removal rate of zinc, sulfur, and carbon can be maintained high by exceeding 70°C. However, if the liquid temperature exceeds 90°C, the removal rate of zinc, sulfur, and carbon will not be significantly improved and the loss of water by evaporation will be excessive, which is disadvantageous in terms of cost.

[0041] The washing time of the second alkaline washing step is preferably 0.50 hours or more and 2.0 hours or less, and more preferably 0.75 hours or more and 1.0 hours or less, similar to the first alkaline washing step. Since the particles of the nickel-cobalt mixed hydroxide generated in the thermal decomposition precipitation step often aggregate to form aggregates, if the washing time is less than 0.50 hours, it is difficult to make the alkaline washing solution reach the inside of the aggregates even if the alkaline washing is performed while stirring, and as a result, it is difficult to obtain the desired removal rate. On the other hand, if the washing time exceeds 2.0 hours, nickel hydroxide and cobalt hydroxide are oxidized to easily generate oxides, and the recovery rate as hydroxides may decrease.

[0042] There is no particular limitation on the specific washing method using an alkaline washing solution, but an example is a method in which nickel-cobalt mixed hydroxide is added to an alkaline washing solution previously placed in a container equipped with a stirrer and a jacket, as in the first alkaline washing step, and the solution is stirred while controlling the temperature by introducing, for example, steam into the jacket, thereby maintaining the solution in a slurry state for a desired period of time. After the alkaline washing, the slurry is introduced into a solid-liquid separator such as a centrifuge or a filter for solid-liquid separation, whereby the alkaline-washed wet nickel-cobalt mixed hydroxide can be recovered.

[0043] In the washing effluent discharged to the liquid phase side in the solid-liquid separation after the above-mentioned alkaline washing, the solubility of the carbon content in the washing effluent decreases if the liquid temperature drops, so in this case too, it is possible to precipitate the carbon content in the washing effluent as sodium carbonate by using a precipitation method similar to the above-mentioned first alkaline washing step. The washing effluent from which the sodium carbonate has been removed in this way can be reused as an alkaline washing liquid.

[0044] As described above, by employing the method for producing a hydroxide containing nickel and cobalt according to the embodiment of the present invention, it is possible to produce a high-purity hydroxide containing nickel and cobalt with extremely few impurities from a crude raw material nickel-cobalt mixed hydroxide represented by nickel-cobalt mixed hydroxide precipitate (MHP) without by-producing sodium sulfate. In particular, even if the crude raw material contains various impurities such as manganese, iron, and aluminum, these impurities can be easily separated and removed, so that the hydroxide can be produced at a lower cost than when expensive refined metallic nickel is used as a raw material.

[0045] In addition, in the method for producing hydroxides containing nickel and cobalt according to the embodiment of the present invention, the raw material is washed in two separate steps using different washing solutions in the water washing step and the first alkali washing step before being treated in the pyrolysis precipitation step. Therefore, when MHP is used as the raw material, most of the impurities such as calcium, magnesium, zinc, sulfur, and silicon generally contained in the MHP can be removed. Therefore, the quality of the mixed hydroxide of nickel and cobalt obtained through the pyrolysis precipitation step can be significantly improved compared to that of the raw material MHP. Next, the present invention will be described in more detail with reference to reference examples and examples, but the present invention is not limited to the following reference examples and examples. EXAMPLES

[0046] [Reference Example 1] (Air injection test in the pyrolysis precipitation process) An aqueous solution containing 28.82 g of ammonium carbonate ((NH4)2CO3) was added to 185 mL of pure water and 15 mL of 25% ammonia water placed in a container to prepare an ammonium carbonate solution with an ammonium carbonate concentration of 1.5 mol / L. 20 g of nickel-cobalt mixed hydroxide was added to the resulting ammonium carbonate solution to make a slurry, which was then stirred with a stirrer and held at 20°C for 2.0 hours while controlling the liquid temperature, thereby carrying out a leaching treatment.

[0047] After the above leaching treatment, the leaching residue was removed by solid-liquid separation by filtration, the obtained leaching solution was placed in a 500 mL separable flask and marked so that the liquid volume could be confirmed, and stirring was started while heating with a hot stirrer so that the temperature was 80°C or higher, and evaporated water was replenished with pure water. When the temperature reached 80°C, air was started to be blown in at a flow rate of 1.0 L / min, and the thermal decomposition treatment was carried out in this state for 6 hours. The resulting slurry containing the precipitate was filtered with a filter to recover the nickel-cobalt mixed hydroxide of sample 1 on the solid phase side. The obtained nickel-cobalt mixed hydroxide of sample 1 was dried and then quantitatively analyzed by inductively coupled plasma atomic emission spectrometry (ICP-AES) to determine the recovery rates of nickel and cobalt.

[0048] For comparison, a precipitate was produced in the same manner as above, except that air was not blown in during the thermal decomposition treatment, and this was filtered in the same manner as above to recover the nickel-cobalt mixed hydroxide of sample 2. The nickel-cobalt mixed hydroxide of sample 2 obtained was dried and quantitatively analyzed in the same manner as above to determine the recovery rates of nickel and cobalt. The recovery rates of nickel and cobalt of samples 1 and 2 are shown in Table 1 below.

[0049] [Table 1]

[0050] As can be seen from the results in Table 1 above, the cobalt recovery rate was significantly higher in Sample 1 than in Sample 2. This is thought to be because by blowing air into the sample while stirring during the thermal decomposition treatment, the divalent cobalt after the thermal decomposition of the ammine complex was efficiently oxidized to trivalent cobalt, thereby promoting the recovery of cobalt hydroxide.

[0051] [Reference Example 2] (Alkaline cleaning test in the second alkaline cleaning step) (Experiment A1) 50 mL of an aqueous caustic soda solution with a sodium hydroxide concentration of 4.0 mol / L was placed in a beaker, and 5 g of the mixed hydroxide of nickel and cobalt recovered by the thermal decomposition treatment in Reference Example 1 was added to form a slurry, which was then kept at a liquid temperature of 80° C. for 1.0 hour while stirring and mixing. After this alkaline washing, the slurry was subjected to solid-liquid separation by filtration, and the washing wastewater containing impurities was removed to obtain a hydroxide containing nickel and cobalt.

[0052] (Experiment A2) The mixed hydroxide of nickel and cobalt was treated in the same manner as in Experiment A1 above, except that 50 mL of an aqueous solution of caustic soda with a concentration of 6.0 mol / L was used instead of the 4.0 mol / L sodium hydroxide.

[0053] (Experiment A3) The mixed hydroxide of nickel and cobalt was treated in the same manner as in Experiment A1 above, except that 50 mL of an aqueous solution of caustic soda with a concentration of 8.0 mol / L was used instead of the 4.0 mol / L sodium hydroxide.

[0054] The alkaline washing conditions for the above experiments A1 to A3, the respective removal rates of zinc, sulfur, and carbon by the alkaline washing, and the zinc, sulfur, and carbon contents in the mixed hydroxide after the alkaline washing are shown in Table 2 below. The removal rates shown in Table 2 were determined from the material balance of the zinc, sulfur, and carbon contents obtained by quantitatively analyzing the post-washing liquid (washing wastewater) and the post-washing mixed hydroxide (NiCo mixed hydroxide). For example, in the case of zinc, the zinc content L was calculated by multiplying the zinc concentration obtained by quantitatively analyzing the post-washing liquid by the amount of the post-washing liquid. Zn The zinc content S is calculated by multiplying the zinc content obtained by quantitatively analyzing the mixed hydroxide (dry matter) after washing by the dry matter weight of the mixed hydroxide. Zn Calculate the content of both L Zn , S Zn The removal rate was calculated by substituting the above into the following formula 2. [Formula 2] Removal rate=L Zn / (L Zn +S Zn )·100

[0055] [Table 2]

[0056] As can be seen from Table 2 above, by performing alkaline washing using a caustic soda aqueous solution with a sodium hydroxide concentration of 4.0 mol / L or more and 8.0 mol / L or less, it is possible to maintain a removal rate of 80% or more for carbon and sulfur, and the removal rate of zinc can be improved by increasing the concentration of sodium hydroxide. The zinc removal rate was inferior to that in Reference Example 3 described below. This is thought to be because zinc exists in a form contained in the mixed hydroxide of nickel and cobalt recovered in the thermal decomposition precipitation process, making it difficult for the alkaline washing solution to come into contact with zinc. Note that all of the mixed hydroxides in Experiments A1 to A3 had a quality that could be used as a material for the positive electrode active material of a lithium ion secondary battery.

[0057] [Reference Example 3] (Alkaline cleaning test in the first alkaline cleaning step) (Experiment B1) As raw materials, 400g (dry weight) of MHP and 1.85L of pure water were placed in a beaker, and then the slurry temperature was maintained at 20°C while stirring and mixing for 30 minutes to perform water washing. After the water washing, the washing liquid was separated and removed by filtration, and 14g of the solid nickel-cobalt mixed hydroxide was added to a beaker containing 140mL of a caustic soda solution with a sodium hydroxide concentration of 6.0mol / L, and alkaline washing was performed by maintaining the liquid temperature at 20°C while stirring and mixing for 2.0 hours. After this alkaline washing, the slurry was separated into solid and liquid by filtration, and the washing wastewater containing impurities was removed to obtain nickel-cobalt mixed hydroxide.

[0058] (Experiment B2) The nickel-cobalt mixed hydroxide was subjected to water washing and alkaline washing in the same manner as in Experiment B1, except that the liquid temperature during alkaline washing was changed from 20°C to 80°C.

[0059] (Experiment B3) The nickel-cobalt mixed hydroxide was subjected to water washing and alkali washing in the same manner as in Experiment B1, except that 140 mL of a caustic soda solution with a sodium hydroxide concentration of 4.0 mol / L was used instead of 6.0 mol / L, the temperature during the alkali washing was changed to 80°C instead of 20°C, and the retention time of the alkali washing was changed to 1.0 hour instead of 2.0 hours.

[0060] (Experiment B4) The nickel-cobalt mixed hydroxide was subjected to water washing and alkaline washing in the same manner as in Experiment B1, except that the liquid temperature during alkaline washing was changed to 80°C instead of 20°C, and the holding time of alkaline washing was changed to 1.0 hour instead of 2.0 hours.

[0061] (Experiment B5) The nickel-cobalt mixed hydroxide was subjected to water washing treatment and alkali washing treatment in the same manner as in Experiment B4, except that 140 mL of an aqueous caustic soda solution having a concentration of 8.0 mol / L was used instead of 6.0 mol / L of sodium hydroxide.

[0062] (Experiment B6) The nickel-cobalt mixed hydroxide was subjected to water washing treatment and alkali washing treatment in the same manner as in Experiment B3, except that the retention time for the alkali washing was changed to 0.50 hours instead of 1.0 hour.

[0063] (Experiment B7) The nickel-cobalt mixed hydroxide was subjected to water washing treatment and alkali washing treatment in the same manner as in Experiment B3, except that the retention time for the alkali washing was changed to 2.0 hours instead of 1.0 hour.

[0064] (Experiment B8) The nickel-cobalt mixed hydroxide was subjected to water washing treatment and alkali washing treatment in the same manner as in Experiment B4, except that the retention time for the alkali washing was changed to 0.50 hours instead of 1.0 hour.

[0065] (Experiment B9) The nickel-cobalt mixed hydroxide was subjected to water washing treatment and alkali washing treatment in the same manner as in Experiment B4, except that the retention time for the alkali washing was changed to 2.0 hours instead of 1.0 hour.

[0066] (Experiment B10) The nickel-cobalt mixed hydroxide was subjected to water washing treatment and alkali washing treatment in the same manner as in Experiment B5, except that the retention time for the alkali washing was changed to 0.50 hours instead of 1.0 hour.

[0067] (Experiment B11) The nickel-cobalt mixed hydroxide was subjected to water washing treatment and alkali washing treatment in the same manner as in Experiment B5, except that the retention time for the alkali washing was changed to 2.0 hours instead of 1.0 hour.

[0068] The alkaline washing conditions in the above Experiments B1 to B11, the respective removal rates of zinc and sulfur by the alkaline washing, and the contents of zinc, sulfur, and carbon in the mixed hydroxide (NiCo mixed hydroxide) after the alkaline washing are shown in the following Table 3. The removal rates and contents in Table 3 were determined in the same manner as in Reference Example 2.

[0069] [Table 3]

[0070] As can be seen from Table 3 above, by using a caustic soda solution with a sodium hydroxide concentration of 4.0 mol / L or more and 8.0 mol / L or less, and by performing alkaline cleaning under conditions where the liquid temperature during cleaning is 20°C or more and 80°C or less and the cleaning time is 0.50 hours or more and 2.0 hours or less, it is possible to remove zinc at a removal rate of 15% or more and sulfur at a removal rate of 75% or more.

[0071] [Reference Example 4] (Ammonium carbonate leaching test in the leaching process) (Experiment C1) An aqueous solution containing 28.82 g of ammonium carbonate ((NH4)2CO3) was added to 185 mL of pure water and 15 mL of ammonia water with a concentration of 25% by mass placed in a container, to prepare an aqueous solution containing ammonia with an ammonium carbonate concentration of 1.5 mol / L. The resulting aqueous solution containing ammonia was mixed with 20 g of powdered nickel-cobalt mixed hydroxide (MHP) having the composition shown in Table 4 below to form a slurry, which was stirred with a stirrer and held at a liquid temperature of 20°C for 2.0 hours to carry out a leaching treatment.

[0072] [Table 4]

[0073] After the above leaching treatment, solid-liquid separation was performed by filtration, and a leaching residue with a dry mass of 10.8 g and a leaching solution of 270 mL were obtained. The element concentrations of the leaching residue and the leaching solution were measured by inductively coupled plasma atomic emission spectrometry (ICP-AES), and the leaching rate of each element was calculated by the following formula 3. [Formula 3] Leaching rate of element α = mass of element α in leaching solution / (mass of element α in leaching solution + mass of element α in leaching residue) x 100

[0074] As a result, the leaching rate of nickel was 71.2%, and that of cobalt was 65.3%, and a leachate consisting of an aqueous ammonia solution containing a large amount of nickel ions and cobalt ions was produced.

[0075] (Experiment C2) The leaching treatment of MHP and the subsequent solid-liquid separation were carried out in the same manner as in Experiment C1, except that the amount of ammonium carbonate ((NH4)2CO3) added was changed from 28.82g to 57.65g to prepare an ammonia-containing aqueous solution with an ammonium carbonate concentration of 3.0mol / L. A leaching residue with a dry mass of 6.30g and a leachate of 310mL were obtained. The elemental concentrations of the obtained leachate residue and leachate were measured in the same manner as in Experiment C1, and the leaching rate of nickel was 90.3% and the leachate rate of cobalt was 84.6%, indicating that a leachate consisting of an aqueous ammonia solution containing a large amount of nickel ions and cobalt ions was produced.

[0076] (Experiment C3) The leaching treatment of MHP and the subsequent solid-liquid separation were carried out in the same manner as in Experiment C1, except that the amount of ammonium carbonate ((NH4)2CO3) added was changed from 28.82g to 115.30g to prepare an ammonia-containing aqueous solution with an ammonium carbonate concentration of 4.1mol / L. A leaching residue with a dry mass of 5.53g and a leachate of 355mL were obtained. The elemental concentrations of the obtained leachate residue and leachate were measured in the same manner as in Experiment C1, and the leaching rate of nickel was 94.4% and the leachate rate of cobalt was 88.9%, indicating that a leachate consisting of an aqueous ammonia solution containing a large amount of nickel ions and cobalt ions was produced.

[0077] (Test C4) Leaching of MHP and subsequent solid-liquid separation were carried out in the same manner as in Experiment C1, except that the liquid temperature during leaching was changed from 20°C to 50°C, and a leaching residue with a dry mass of 6.07g and a leachate of 203mL were obtained. The element concentrations of the obtained leachate residue and leachate were measured in the same manner as in Experiment C1, and the leaching rate of nickel was 73.9% and the leaching rate of cobalt was 73.6%, indicating that a leachate consisting of an aqueous ammonia solution containing large amounts of nickel ions and cobalt ions could be produced.

[0078] (Test C5) Leaching of MHP and subsequent solid-liquid separation were carried out in the same manner as in Experiment C2, except that the liquid temperature during leaching was changed from 20°C to 50°C, and a leaching residue with a dry mass of 3.57g and a leachate of 235mL were obtained. The elemental concentrations of the obtained leachate residue and leachate were measured in the same manner as in Experiment C1, and the leaching rate of nickel was 92.5% and the leaching rate of cobalt was 87.3%, indicating that a leachate consisting of an aqueous ammonia solution containing large amounts of nickel ions and cobalt ions could be produced.

[0079] (Experiment C6) Leaching of MHP and subsequent solid-liquid separation were carried out in the same manner as in Experiment C3, except that the liquid temperature during the leaching treatment was changed from 20°C to 50°C, and a leaching residue with a dry mass of 5.05g and a leachate of 415mL were obtained. The element concentrations of the obtained leachate residue and leachate were measured in the same manner as in Experiment C1, and the leaching rate of nickel was 95.2% and the leaching rate of cobalt was 89.2%, indicating that a leachate consisting of an aqueous ammonia solution containing large amounts of nickel ions and cobalt ions could be produced.

[0080] (Experiment C7) 20 g of powdered nickel-cobalt mixed hydroxide (MHP) having the composition shown in Table 4 above was mixed with 25% ammonia water placed in a container to form a slurry, which was then stirred with a stirrer while controlling the liquid temperature at 20°C and held for 2.0 hours to carry out leaching treatment. Thereafter, solid-liquid separation was carried out in the same manner as in Experiment C1 to obtain 150 mL of leachate. The element concentrations of this leachate were measured in the same manner as in Experiment C1 to determine the leaching rate of each element.

[0081] As a result, the leaching rate of nickel was 14.6%, and that of cobalt was 0.2%, which means that the leaching of nickel ions was insufficient and the leaching of cobalt ions was almost not performed compared to experiments C1 to C3, in which the leaching treatment was performed at the same temperature. In this experiment C7, the leaching rate of each element was calculated using the following formula 4. [Formula 4] Leaching rate of element α = mass of element α in leaching solution / mass of element α in MHP × 100

[0082] (Experiment C8) The leaching of MHP and the subsequent solid-liquid separation and concentration measurement were carried out in the same manner as in experiment C7, except that the liquid temperature during the leaching treatment was changed from 20°C to 50°C. The nickel leaching rate was 17.5% and the cobalt leaching rate was 0.3%, which was insufficient for nickel ions compared to experiments C4 to C6, in which the leaching treatment was carried out at the same temperature, and almost no cobalt ions were leached. The leaching rates were calculated in the same manner as in experiment C7. The measurement results of the above experiments C1 to C8 are summarized in Table 5 below.

[0083] [Table 5]

[0084] [Reference Example 5] (Oxygen blowing leaching test of NiCo mixed sulfide (MS)) (Experiment D1) An aqueous solution containing 28.82 g of ammonium carbonate ((NH4)2CO3) was added to 185 mL of pure water and 15 mL of ammonia water with a concentration of 25 mass% placed in a container, to prepare an aqueous solution containing ammonia with an ammonium carbonate concentration of 1.5 mol / L. 18 g of powdered nickel-cobalt mixed sulfide (MS) having the composition shown in Table 6 below was mixed with the resulting aqueous solution containing ammonia to prepare a slurry. While blowing oxygen gas from an oxygen cylinder into the slurry at a flow rate of 1 L / min, the mixture was stirred with a stirrer and held at a liquid temperature of 50°C for 2 hours to perform a leaching treatment.

[0085] [Table 6]

[0086] After the above leaching treatment, solid-liquid separation was performed by filtration, and a leaching residue with a dry mass of 15.2 g and a leaching solution of 205 mL were obtained. The element concentrations of the leaching residue and the leaching solution were measured by inductively coupled plasma atomic emission spectrometry (ICP-AES), and the leaching rate of each element was calculated by the following formula 5. [Formula 5] Leaching rate of element α = mass of element α in leaching solution / (mass of element α in leaching solution + mass of element α in leaching residue) x 100

[0087] As a result, the leaching rate of nickel was 18.3% and that of cobalt was 7.2%, and a leachate consisting of an aqueous ammonia solution containing a large amount of nickel ions and cobalt ions was produced.

[0088] (Experiment D2) The leaching treatment of MS and the subsequent solid-liquid separation were carried out in the same manner as in Experiment D1, except that the amount of ammonium carbonate ((NH4)2CO3) added was changed from 28.82g to 57.65g to prepare an ammonia-containing aqueous solution with an ammonium carbonate concentration of 3.0mol / L. A leaching residue with a dry mass of 9.80g and a leachate of 238mL were obtained. The elemental concentrations of the obtained leachate residue and leachate were measured in the same manner as in Experiment D1, and the leachate leaching rate of nickel was 44.7% and the leachate leaching rate of cobalt was 24.5%, indicating that a leachate consisting of an aqueous ammonia solution containing a large amount of nickel ions and cobalt ions was produced.

[0089] (Experiment D3) The leaching treatment of MS and the subsequent solid-liquid separation were carried out in the same manner as in Experiment D1, except that the amount of ammonium carbonate ((NH4)2CO3) added was changed from 28.82g to 115.30g to prepare an ammonia-containing aqueous solution with an ammonium carbonate concentration of 4.1mol / L. A leaching residue with a dry mass of 7.84g and a leachate of 200mL were obtained. The elemental concentrations of the obtained leachate residue and leachate were measured in the same manner as in Experiment D1, and the leachate rate of nickel was 45.1% and the leachate rate of cobalt was 39.4%, indicating that a leachate consisting of an aqueous ammonia solution containing a large amount of nickel ions and cobalt ions was produced.

[0090] (Experiment D4) Leaching of MS and subsequent solid-liquid separation were carried out in the same manner as in Experiment D2, except that the liquid temperature during the leaching treatment was changed from 50°C to 20°C, and a leaching residue with a dry mass of 12.6 g and a leachate of 220 mL were obtained. The element concentrations of the obtained leachate residue and leachate were measured in the same manner as in Experiment D1, and the leaching rate of nickel was 27.7%, and the leaching rate of cobalt was 21.6%, indicating that a leachate consisting of an aqueous ammonia solution containing large amounts of nickel ions and cobalt ions could be produced.

[0091] (Experiment D5) In experiment D1, ammonium carbonate was used in the leaching treatment, but this was replaced with ammonium bicarbonate, and the rest of the experiment was conducted in the same manner as in experiment D1. As a result, it was confirmed that a leachate consisting of an aqueous ammonia solution containing large amounts of nickel ions and cobalt ions almost equivalent to those in experiment D1 was obtained.

[0092] (Experiment D6) The leaching of MS and the subsequent solid-liquid separation were carried out in the same manner as in experiment D1, except that 200 mL of ammonia water with a concentration of 25% was used instead of the ammonia-containing aqueous solution containing ammonium carbonate as the leaching solution, and 200 mL of leaching solution was obtained. The element concentrations of this leaching solution were measured in the same manner as in experiment D1 to determine the leaching rate of each element. As a result, the leaching rate of nickel was 14.6%, and the leaching rate of cobalt was 0.2%, which was insufficient for nickel ions compared to experiments D1 to D3 in which the leaching treatment was carried out at the same temperature, and almost no cobalt ions were leached. In this experiment D6, the leaching rate of each element was calculated using the following formula 6. [Formula 6] Leaching rate of element α = mass of element α in leaching solution / mass of element α in MS × 100

[0093] (Experiment D7) The leaching of MS and the subsequent solid-liquid separation and concentration measurement were carried out in the same manner as in experiment D6, except that the liquid temperature during the leaching treatment was changed from 50°C to 20°C. The nickel leaching rate was 14.6% and the cobalt leaching rate was 0.2%, which was insufficient for nickel ions compared to experiment D4, in which the leaching treatment was carried out at the same temperature, and almost no cobalt ions were leached. The leaching rates were calculated in the same manner as in experiment D6. The measurement results of experiments D1 to D7, excluding experiment D5, are summarized in Table 7 below.

[0094] [Table 7]

[0095] [Reference Example 6] (Pyrolysis and precipitation test of NiCo mixed sulfide (MS) leachate) An aqueous solution containing 28.82 g of ammonium carbonate ((NH4)2CO3) was added to 185 mL of pure water and 15 mL of ammonia water with a concentration of 25 mass% placed in a container, to prepare an aqueous solution containing ammonia with an ammonium carbonate concentration of 1.5 mol / L. 18 g of powdered nickel-cobalt mixed sulfide (MS) having the composition shown in Table 6 above was mixed with the resulting aqueous solution containing ammonia to prepare a slurry. The resulting slurry was stirred with a stirrer and held at a temperature of 20°C for 2 hours to carry out a leaching treatment.

[0096] After the above leaching treatment, the leaching residue was removed by solid-liquid separation by filtration, and the obtained leaching solution consisting of an ammonia solution of nickel and cobalt was placed in a 500 mL separable flask and marked so that the liquid volume could be confirmed. Stirring was started while heating with a hot stirrer so that the temperature reached 80°C or higher, and the evaporated water was replenished with pure water. Pyrolysis treatment was carried out for 6 hours from the point at which it was confirmed that the temperature had risen to 80°C. The resulting slurry containing the precipitate was filtered through a filter to separate and recover the nickel and cobalt hydroxides from the decomposition liquid. The obtained hydroxides were dried and then quantitatively analyzed by inductively coupled plasma atomic emission spectroscopy (ICP-AES), and the recovery rates of nickel and cobalt hydroxides were 70.8% and 85.8%, respectively.

[0097] [Example 1] The raw material, nickel-cobalt mixed hydroxide (MHP), was treated according to the block flow diagram in Figure 1. Specifically, first, in the water washing process, 400 g (dry weight) of MHP as the raw material and 1.85 L of pure water were placed in a beaker, and the water was washed by stirring and mixing while maintaining the water temperature at 20°C.

[0098] Next, in the first alkaline washing step, 381.4 g (dry weight) of MHP obtained by the above water washing treatment was placed in a beaker together with 1.55 L of an 8.0 mol / L aqueous sodium hydroxide solution, and alkaline washing was performed by stirring and mixing while adjusting the temperature to 20° C. The washing time was 0.50 hours.

[0099] Next, in the leaching process, 183 g (dry weight) of MHP that had been alkaline washed in the first alkaline washing process was placed in a beaker together with 1.0 L of a 25% ammonia aqueous solution, 0.6 L of pure water, and 253 g of ammonium hydrogen carbonate, and the temperature was adjusted to 20°C while stirring and mixing to perform the leaching treatment. The ammonium hydrogen carbonate concentration at this time was 2.0 mol / L.

[0100] Next, in the thermal decomposition precipitation process, 1.6 L of the leachate obtained by the above leaching treatment was placed in a beaker, heated to a temperature of 80°C, and held at this temperature for 2.0 hours to generate a mixed hydroxide of nickel and cobalt. Stirring was continued while holding at the above heating temperature. After that, solid-liquid separation was performed to obtain a mixed hydroxide of nickel and cobalt on the solid phase side, and a liquid after solid-liquid separation on the liquid phase side.

[0101] Finally, in the second alkaline washing step, 89 g (dry weight) of the mixed hydroxide of nickel and cobalt obtained in the above thermal decomposition and precipitation step was placed in a beaker together with 0.83 L of an 8.0 mol / L aqueous sodium hydroxide solution, and alkaline washing was performed by stirring and mixing while adjusting the temperature to 20°C. The washing time was 0.50 hours. The composition (quality) of the MHP used as the raw material and the intermediate products generated in each of the above series of steps was determined by quantitative analysis using inductively coupled plasma atomic emission spectroscopy (ICP-AES), as shown in Table 8 below.

[0102] [Table 8]

[0103] From the results in Table 8 above, it was found that by sequentially going through the water washing step, the first alkali washing step, the leaching step, the thermal decomposition precipitation step, and the second alkali washing step that satisfy the requirements of the present invention, it is possible to produce a hydroxide containing nickel and cobalt having a quality usable as a precursor for a positive electrode active material for a lithium ion battery, even if the raw material contains a relatively large amount of impurities in addition to the target metals nickel and cobalt.

[0104] [Example 2] In Example 1, ammonium hydrogen carbonate was used in the leaching step, but except for replacing it with ammonium carbonate, the same procedure was carried out as in Example 1. As a result, it was confirmed that the mixed hydroxide of nickel and cobalt obtained through the second alkali washing step had a quality almost equivalent to that shown in Table 8 above.

[0105] As described above, even when ammonium carbonate is used instead of ammonium hydrogen carbonate, by sequentially going through the water washing step, the first alkali washing step, the leaching step, the thermal decomposition precipitation step, and the second alkali washing step that satisfy the requirements of the present invention, it is possible to produce a hydroxide containing nickel and cobalt that can be used as a precursor of a positive electrode active material for a lithium ion battery, even if the raw material contains a relatively large amount of impurities in addition to the target metals nickel and cobalt.

Claims

1. A water washing step of washing the particulate nickel-cobalt mixed hydroxide with water; A first alkali washing step in which the water-washed nickel-cobalt mixed hydroxide is washed with an aqueous sodium hydroxide solution having a sodium hydroxide concentration of 1.0 mol / L to 8.0 mol / L and a liquid temperature of 10° C. to 90° C. for 0.50 hours to 2.0 hours; a leaching step in which the nickel-cobalt mixed hydroxide washed in the first alkaline washing step is leached in a slurry state at a temperature of 0° C. to 60° C. using an ammonia-containing aqueous solution containing ammonia water having an ammonium carbonate and / or ammonium hydrogen carbonate concentration of 0.50 mol / L to 4.1 mol / L; a thermal decomposition and precipitation step in which the leachate containing nickel and cobalt obtained by the leaching treatment is heated at 60° C. to 100° C. for 0.50 hours to 2.0 hours to precipitate the nickel and cobalt as hydroxides; and a second alkali washing step of washing the precipitated hydroxide with an aqueous sodium hydroxide solution having a sodium hydroxide concentration of 1.0 mol / L or more and 8.0 mol / L or less and a liquid temperature of 10°C or more and 90°C or less for 0.50 hours or more and 2.0 hours or less.

2. The method for producing a hydroxide containing nickel and cobalt according to claim 1, wherein air is blown into the leachate in the thermal decomposition and precipitation step.

3. 3. The method for producing a hydroxide containing nickel and cobalt according to claim 1, wherein the aqueous sodium hydroxide solution used in the first alkaline washing step and / or the second alkaline washing step has a sodium hydroxide concentration of 4.0 mol / L or more and 8.0 mol / L or less and a liquid temperature of 70° C. or more and 90° C. or less.

Citation Information

Patent Citations

  • Reductive ammonia leaching of nickel and cobalt supported materials

    JP2006522866A

  • Production method for a composite compound comprising nickel and cobalt

    WO2012020768A1

  • Method for manufacturing nickel and cobalt-containing solution from hydroxide containing nickel and cobalt

    WO2020196046A1

  • Production of nickel hydroxide from elemental nickel

    JP1998324524A